The idea is to solve the equation -3x2 + 24x - 19 = 0. You can use the quadratic formula for this, using a = -3, b = 24, c = 19.
Or complete the square since dividing by -3 will give us 8x, an even coefficient.
-3x2 + 24x - 19 = 0 (add and subtract 48 to the left side)
-3x2 + 24x -48 + 29 = 0 (subtract 29 to both sides, and factor out -3)
-3(x2 - 8x + 16) = -29 (divide by -3 to both sides)
(x - 4)2 = 29/3
x - 4 = ± √(29/3) (add 4 to both sides)
x = 4 ± √(29/3) (multiply by 3/3 inside the radical, if you want to rationalize the denominator)
x = 4 ± (√87)/3
54.3 squared
(5w + 1)(w + 1)
negative b plus or minus the square root of b squared minus 4AC all over 2 A
hello
"minus negative x" means "plus x" (2x - 5)(x + 2) or (2x + 5)(x - 2) depending on what you really meant...
54.3 squared
(5w + 1)(w + 1)
The quotient of a positive integer by a negative is always negative. Say this to yourself a couple times: "MULTIPLICATION: minus times minus is plus (negative x negative = positive).....minus times plus is minus (negative x positive = negative).....plus times plus is plus (positive x positive = positive) DIVISION: minus divi minus is plus (negative ÷ negative = positive)......minus divi plus is minus (negative ÷ positive = negative).....plus divi plus is plus (positive ÷ positive = positive)"
x equals negative b plus or minus the square root of b squared minus 4bc over 2a
negative b plus or minus the square root of b squared minus 4AC all over 2 A
I honestly don't know :D but heres something to help you "MULTIPLICATION: minus times minus is plus (negative x negative = positive).....minus times plus is minus (negative x positive = negative).....plus times plus is plus (positive x positive = positive) DIVISION: minus divi minus is plus (negative ÷ negative = positive)......minus divi plus is minus (negative ÷ positive = negative).....plus divi plus is plus (positive ÷ positive = positive)"
hello
"minus negative x" means "plus x" (2x - 5)(x + 2) or (2x + 5)(x - 2) depending on what you really meant...
Let square = [x] -4+3*(-2)*[-4]+[3x-2x]=-4-6-2+[x]=-12+[x]The answer is negative 12 plus squared x.
Four squared plus 188,898 minus 17,798 plus 188,898 = 360,014
Factor out -2: -2(x squared +11x-20). This is fully factored.
-22 - -22